Pediatric Nutritional Assessment - Helisa Rachel Patrice Sianipar; Jully Neily Kasie; Yuda Satrio Wicaksono (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Pediatric nutrition plays a vital role in the growth and development of children. It not only meets the daily nutritional needs of healthy children but also supports their normal growth. In contrast, for unhealthy children, it aims to prevent growth delays and developmental issues, especially in cognitive functions. The situation in Indonesia presents a unique challenge with the coexistence of undernutrition and overnutrition, both having significant short-term and long-term health impacts. Discussion: In the realm of pediatric nutrition, malnutrition manifests in various forms. Nutritional deficiencies such as wasting, stunting, and being underweight arise from inadequate dietary intake. Additionally, there are concerns about micronutrient malnutrition, which includes both deficiencies and excesses of vital nutrients. Overnutrition, leading to obesity and associated chronic diseases, is also a significant problem. The approach to pediatric nutritional care is multi-faceted, involving the assessment of nutritional status, determination of individual caloric needs, and selecting the appropriate method for nutrition delivery, whether it be oral, enteral, or parenteral. Monitoring and evaluating the effectiveness of these interventions is a critical ongoing process. An important aspect of preventive care includes educating parents about proper feeding techniques, such as establishing regular meal times and understanding the child's hunger and satiety signals, to avoid feeding difficulties. For cases like Failure to Thrive (FTT), where children do not meet standard growth metrics, careful management is necessary to ensure adequate nutrition and to prevent complications like refeeding syndrome. Conclusion: Effective pediatric nutrition requires a holistic and personalized approach. It is crucial in addressing the dual burden of undernutrition and overnutrition in Indonesia. By implementing proper nutritional care and structured feeding practices, children's health outcomes can be significantly improved, supporting their growth and developmental processes.